AI-Powered Energy Harvesting Systems in Urban Infrastructure: A New Era in Electrical Engineering and Civil Automation (American Journal of Multidisciplinary Research and Innovation, 2025)
The incorporation of Artificial Intelligence technologies within energy harvesting schemes represents a paradigm shift for urban infrastructure, making efficient and environmentally sustainable energy access feasible. This article investigates the interplay of AI with energy-harvesting technologies in the context of urban living, concentrating on progress made in ambient-energy harvesting. It reviews different classes of energy harvesting, including piezoelectric, solar and thermoelectric, and their inclusion in AI-powered optimisation models. The study emphasises how AI can improve the performance of these systems through real-time data analysis, predictive maintenance and energy management. Key results indicate that AI enhanced the utility of energy harvesting by resource allocation, reducing unnecessary energy wasted and enabling self-sufficient smart cities. In addition to the above, this review discusses system integration, data privacy, and scalability as challenges that need to be probed into for the universal deployment of AI-driven energy harvesting technologies. The principal message from the study is that AI, if properly assimilated, stands as a main driver to introduce a sustainable era of urban interconnected energy solutions leading toward cleaner and more efficient/cheaper energy systems.